The sleep–wake cycle and Alzheimer's disease: what do we know?. (October 2014) - Lim, Miranda M; Gerstner, Jason R; Holtzman, David M
SUMMARY : Sleep–wake disturbances are a highly prevalent and often disabling feature of Alzheimer's disease (AD). A cardinal feature of AD includes the formation of amyloid plaques, associated with the extracellular accumulation of the amyloid-β (Aβ) peptide. Evidence from animal and human studies suggests that Aβ pathology may disrupt the sleep–wake cycle, in that as Aβ accumulates, more sleep–wake fragmentation develops. Furthermore, recent research in animal and human studies suggests that the sleep–wake cycle itself may influence Alzheimer's disease onset and progression. Chronic sleep deprivation increases amyloid plaque deposition, and sleep extension results in fewer plaques in experimental models. In this review geared towards the practicing clinician, we discuss possible mechanisms underlying the reciprocal relationship between the sleep–wake cycle and AD pathology and behavior, and present current approaches to therapy for sleep disorders in AD.